Wild-Type MIC Distributions and Epidemiological Cutoff Values for the Echinocandins and Candida spp. - Pfaller, M. A. (American Society for Microbiology (ASM), 2010)
We tested a global collection of Candida sp. strains against anidulafungin, caspofungin, and micafungin, using CLSI M27-A3 broth microdilution (BMD) methods, in order to define wild-type (WT) populations and epidemiological cutoff values (ECVs). From 2003 to 2007, 8,271 isolates of Candida spp. (4,283 C. albicans, 1,236 C. glabrata, 1,238 C. parapsilosis, 996 C. tropicalis, 270 C. krusei, 99 C. lusitaniae, 88 C. guilliermondii, and 61 C. kefyr isolates) were obtained from over 100 centers worldwide. The modal MICs (in μg/ml) for anidulafungin, caspofungin, and micafungin, respectively, for each species were as follows: C. albicans, 0.03, 0.03, 0.015; C. glabrata, 0.06, 0.03, 0.015; C. tropicalis, 0.03, 0.03, 0.015; C. kefyr, 0.06, 0.015, 0.06; C. krusei, 0.03, 0.06, 0.06; C. lusitaniae, 0.05, 0.25, 0.12; C. parapsilosis, 2, 0.25, 1; and C. guilliermondii, 2, 0.5. 05. The ECVs, expressed in μg/ml (percentage of isolates that had MICs that were less than or equal to the ECV is shown in parentheses) for anidulafungin, caspofungin, and micafungin, respectively, were as follows: 0.12 (99.7%), 0.12 (99.8%), and 0.03 (97.7%) for C. albicans; 0.25 (99.4%), 0.12 (98.5%), and 0.03 (98.2%) for C. glabrata; 0.12 (98.9%), 0.12 (99.4%), and 0.12 (99.1%) for C. tropicalis; 0.25(100%), 0.03 (100%), and 0.12 (100%) for C. kefyr; 0.12 (99.3%), 0.25 (96.3%), and 0.12 (97.8%) for C. krusei; 2 (100%), 0.5 (98.0%), and 0.5 (99.0%) for C. lusitaniae; 4 (100%), 1 (98.6%), and 4 (100%) for C. parapsilosis; 16 (100%), 4 (95.5%), and 4 (98.9%) for C. guilliermondii. These WT MIC distributions and ECVs will be useful in surveillance for emerging reduced echinocandin susceptibility among Candida spp. and for determining the importance of various FKS1 or other mutations.